2018
DOI: 10.1097/aap.0000000000000727
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Ropivacaine Concentrations Following Local Infiltration Analgesia in Total Knee Arthroplasty

Abstract: The peak total ropivacaine concentration was below quoted toxic concentrations (2.2 μg/mL) in all patients. This peak occurred later than has previously been described in those undergoing neuraxial or peripheral nerve block, occurring between 6 and 24 hours. The influence of age, weight, and renal function on systemic ropivacaine concentration should be considered when planning local infiltration analgesia. Female sex is a factor that has not previously been associated with peak ropivacaine concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
1
11
1
1
Order By: Relevance
“…The observed Cmax after LIA only in our study was nearly identical to the Cmax demonstrated in the study by Miller et al (0.53 vs 0.57 µg/mL), although our Tmax was shorter than what they reported (4 hours vs 12 hours) 9. It is not clear why there is such a difference in time to peak concentration between our study and that done by Miller et al .…”
Section: Discussionsupporting
confidence: 78%
“…The observed Cmax after LIA only in our study was nearly identical to the Cmax demonstrated in the study by Miller et al (0.53 vs 0.57 µg/mL), although our Tmax was shorter than what they reported (4 hours vs 12 hours) 9. It is not clear why there is such a difference in time to peak concentration between our study and that done by Miller et al .…”
Section: Discussionsupporting
confidence: 78%
“…Blood sampling for the analysis of total ropivacaine concentration was performed only in the QLB group through the right radial artery at 30, 45, 60 min, and 4 hours after the end of QLB 6 15 16. The study’s initial design included the measurement of ropivacaine concentrations at baseline (preblock).…”
Section: Methodsmentioning
confidence: 99%
“…Still, however, maximal serum anesthetic concentrations are at least transiently modified by renal function in addition to age and sex differences, and caution should be taken in patients with impaired kidney function. 43 Other studies have evaluated the efficacy of ACB alone versus ACB and PAI. Grosso et al 44 conducted a randomized control trial comparing patients who received ACB alone versus ACB with a PAI containing bupivacaine and adrenaline.…”
Section: Periarticular Injection and Peripheral Nerve Blockmentioning
confidence: 99%
“…Still, however, maximal serum anesthetic concentrations are at least transiently modified by renal function in addition to age and sex differences, and caution should be taken in patients with impaired kidney function. 43…”
Section: Periarticular Injection and Peripheral Nerve Blockmentioning
confidence: 99%